Strategi Periklanan Akun Instagram @deliciousbali - Kartikasari, Ni Putu Mega; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2018)
ABSTARCT   @deliciousbali is one of a culinary account that is well known in Bali based on social media Instagram. The popularity of @deliciousbali account makes it as a reference to Balinese youngster who are confused about finding a place to eat. By this matter, some of culinary entrepreneurs want to advertise their businesses on @deliciousbali account. The purpose of this study is to find out how the advertising strategy of @deliciousbali Instagram account. The research results show that account of @deliciousbali is having 2 services in the process of delivering the advertisement, first of all the photos were prepared and took by @deliciousbali account, and the second one the photos were prepared by the clients. In the strategy of ‘what to say’ is using only one theme that is modern culinary. Keywords : Advertisement, @deliciousbali account, Instagram